Penataan Pedagang Kaki Lima di Pasar Cik Puan Kota Pekanbaru - Intan Salwa; Sujianto Sujianto (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Cik Puan Market is one of the traditional markets in Pekanbaru. Several phenomena were discovered. One of them is the arrangement of street vendors at Cik Puan market. Where the street vendors at Cik Puan Market sell at the TPS past the operational hours. This research aims to analyze how street vendors are arranged at Cik Puan Market, Pekanbaru City and what factors inhibit this arrangement. In this research, the author used descriptive qualitative research methods. Researchers use the theory of George G. Terry (2006: 342) where the indicators used include 4 (four) indicators, namely, planning, organizing, actuating and controlling. The results of this research indicate that the arrangement of street vendors at Cik Puan Market is not fully optimal. The market still faces several obstacles in carrying out the arrangements. This can be seen from the large number of street vendors who sell past the specified selling time limit. Researchers also found several inhibiting factors in implementing this arrangement, which include human resources that are not yet optimal in terms of quantity and quality, and a lack of awareness among street vendors of the importance of complying with existing regulations.